Pengaruh Switching Cost, Word Of Mouth, Dan Kepuasan Terhadap Loyalitas Pengguna Kartu IM3 Ooredo Indosat (Studi Kasus Pada Mahasiswa Program Studi S1 Manajamen Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Bengkulu) - Aristanti, Dhea Resta; Bahrun, Khairul (Jurnal Fokus Manajemen, 2024)
Indosat, a company operating in the communications services sector, released its product "IM3" as a means of public communication. The aim of this research is to find out whether switching costs, word of mouth, and satisfaction influence the loyalty of IM3 Ooredo Indosat card users.This research was conducted at Muhammadiyah University Bengkulu, involving students from the Management study program, Faculty of Economics and Business, Muhammadiyah University Bengkulu. The type of research used in this research is quantitative research. In this study, the population aimed at was undergraduate management study program students at Muhammadiyah University of Bengkulu who used or used IM3 Ooredo Indosat cards with a total sample of 54 people. The data analysis techniques used are multiple linear regression, coefficient of determination, and hypothesis testing.Based on the research results, the regression equation is Y = 11.725 + 0.231 X1 + 0.180 X2 + 0.430 X3 + e. Switching costs, word of mouth and satisfaction together show an influence on customer loyalty at IM3 OOREDO Indosat Bengkulu.